Experimental methods: Between-subject and within-subject design - Charness, Gary; Gneezy, Uri; Kuhn, Michael A. (Journal of economic behavior & organization, 2012)
► We explore the merits and weaknesses of between-subjects and within-subjects designs in experimental work. ► We describe experiments in economics and in psychology that make comparisons using either of these designs (or both) that sometimes yield the same results and sometimes do not. ► Both have advantages; between-subjects designs are more conservative, but have less power. ► The overall goal is to establish a framework for understanding which critical questions need to be asked about such experimental studies. In this article we explore the issues that surround within-subject and between-subject designs. We describe experiments in economics and in psychology that make comparisons using either of these designs (or both) that sometimes yield the same results and sometimes do not. The overall goal is to establish a framework for understanding which critical questions need to be asked about such experimental studies, what authors of such studies can do to ameliorate fears of confoundedness, and which scenarios are particularly susceptible to divergent results from the two approaches. Overall, we find that both designs have their merits, and the choice of designs should be carefully considered in the context of the question being studied and in terms of the practical implementation of the research study.